Postcoloniality as translation in action - Rajagopalan, Kanavillil (Revista do GEL, 2007)
The postcolonial condition (or what I shall refer to as "postcoloniality", as distinct from "postcolonialism" which is better reserved, I think, for an intellectual movement with a number of distinguishing traits ultimately traceable to certain specific historical conditions) is but another name for the politics of translation as it plays out today (RAJAGOPALAN 2002a). It lays bare the multiplicity of vested interests that have underpinned the history of translation through the ages. Furthermore, it forces us to rethink some of the time-honoured conceptual distinctions such intra-lingual vs. inter-lingual translation by problematising the very notion of "a language" (i.e. language in its individuating sense, as opposed to the generic or abstract senses). The main objective of this paper is to address the phenomenon of increasing hybridisation of the world's languages and its implications for the way we theorise about translation.